Vitamin D levels and clinical outcomes of SARS-CoV-2 Omicron subvariant BA.2 in children: A longitudinal cohort study - Peng, Denggao; Huang, Hua; Liu, Zhichao; Gao, Yanzhang; Liu, Yingxia (Frontiers in Nutrition, 2022)
Objective: To investigate the picture between vitamin D levels and clinical outcomes of SARS-CoV-2 Omicron subvariant BA.2 in children. Methods: A retrospective, longitudinal cohort study was performed. All included hospitalized cases were divided into the sufficient (sVD) and insufficient vitamin D (iVD) groups according to whether their serum 25-hydroxyvitamin D [25(OH)D] concentration was ≥ 30 ng/mL. Dynamic changes in clinical parameters were observed for seven time periods within 28 days after admission. Results: Serum 25(OH)D concentrations were significantly negatively correlated with age in the included cases (r=−0.6; P<0.001). Compared with the iVD group (n=80), the sVD group (n=36) had higher interleukin-6 (18.4 vs 12.9; P=0.003) within the first day; higher procalcitonin within the first (0.15 vs 0.1; P=0.03), 2 to 3 (0.14 vs 0.07; P=0.03), 4 to 5 (0.21 vs 0.07; P=0.02) days; more lymphocytes within the first (1.6 vs 1.2; P=0.02), 2 to 3 (3.7 vs 2; P=0.001), 4 to 5 (3.9 vs 2.1; P=0.01) and 6 to 7 (4.9 vs 2.7; P=0.02) days; notably, higher cycle threshold for N gene (32.9 vs 26.7; P=0.02) or ORF1ab gene (35.2 vs 28.3; P=0.04) within 4 to 5 days. Pneumonia lesions were found in eleven and six cases in the iVD and sVD groups, respectively, without significant difference on computed tomography at admission. Six out of eleven and five out of six had a repeat computed tomography after one to two weeks. Lesion improvement was more significant in the sVD group (P=0.04). Conclusions: Children with vitamin D insufficiency might have poorer clinical outcomes in Omicron subvariant BA.2 infection, especially in older pediatric patients. Further studies are needed to assess effectiveness of supplements in reducing the same.